Depression, anxiety, and stress among frontline health workers during the second wave of COVID-19 in southern Vietnam: A cross-sectional survey. - Anh Le Thi Ngoc; Chinh Dang Van; Phong Nguyen Thanh; Sonia Lewycka; Jennifer Ilo Van Nuil (Public Library of Science (PLoS), 2022)
Health workers around the world have taken on massive frontline roles in the fight against COVID-19, often under intense pressure and in the face of uncertainty. In this study, we determined the rates of depression, anxiety, stress and related factors among health workers in COVID-19 designated hospitals in southern Vietnam during the second wave of COVID-19. From July-September 2020, we collected self-administered surveys from 499 health workers in 14 hospitals that were designated for the care and treatment of patients with COVID-19. The survey included sections on demographics, co-morbid health conditions, symptoms experienced during patient care, a depression, anxiety and stress assessment (DASS-21), and other related factors. We used logistic regression models to identify factors associated with depression, anxiety and stress, and adjusted for confounding factors. 18%, 11.5%, 7.7% of participants had symptoms of depression, anxiety, and stress, respectively with the majority at mild and moderate levels. The risk factors for increased mental health impact included long working hours, experiencing physical symptoms, fear of transmission to family, COVID-19 related stigma, and worry when watching media about COVID-19. Psychological counseling and training in infection prevention were protective factors that reduced the risk of mental health problems. Further exploration of the association between physical symptoms experienced by health workers and mental health may guide interventions to improve health outcomes. More routine COVID-19 testing among health workers could reduce anxieties about physical symptoms and alleviate the fear of transmitting COVID-19 to family and friends. Medical institutions need to ensure that health workers have access to basic trainings prior to initiation of work, and mental health support during the pandemic and into the future.